2022
DOI: 10.3390/nu14153126
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of the Intake of NOVA Classified Ultra-Processed Foods on Syndrome Metabolic Components in Brazilian Adults

Abstract: Longitudinal studies evaluating the relationship between UPF consumption and the incidence of Metabolic Syndrome (MetS) and its components are still scarce. This study aimed to evaluate the effect of UPF consumption on the incidence of MetS and its components in adults. A prospective study was conducted with 896 participants from the 1978/79 Ribeirão Preto cohort, São Paulo, Brazil. UPF consumption was evaluated in %kcal and %g at ages 23–25 years. Incidence of MetS and its components were estimated at ages 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“… 54 , 55 Despite considerable differences in the study population as well as in the amount of UPF consumed (median UPF consumption – Brazil 366 g/day; China 16.3 g/day), higher UPF consumption was associated with increased risk for MetS in both cohorts (4 th vs. 1 st quartile; RR 1.19, 95% CI 1.07-1.32 and HR 1.17, 95% CI 1.01-1.35, in Brazil and China, respectively). In contrast, another study in the Brazilian population (n = 896), 56 with a prolonged follow-up time of 14 years, did not find an association. However, this study was conducted before the use of the NOVA food classification, and as emphasized by the authors, it was not initially designed to accurately measure UPF intake.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“… 54 , 55 Despite considerable differences in the study population as well as in the amount of UPF consumed (median UPF consumption – Brazil 366 g/day; China 16.3 g/day), higher UPF consumption was associated with increased risk for MetS in both cohorts (4 th vs. 1 st quartile; RR 1.19, 95% CI 1.07-1.32 and HR 1.17, 95% CI 1.01-1.35, in Brazil and China, respectively). In contrast, another study in the Brazilian population (n = 896), 56 with a prolonged follow-up time of 14 years, did not find an association. However, this study was conducted before the use of the NOVA food classification, and as emphasized by the authors, it was not initially designed to accurately measure UPF intake.…”
Section: Resultsmentioning
confidence: 69%
“…A 150 g increase in UPF consumption a day was associated with a 4% higher risk of incident MetS (RR = 1.04, 95% CI 1.02–1.06) Pan F. (2023, China) 55 China Nutrition and Health Survey (CNHS) (6 y) n = 5,147 >18 y (50.0%) 24-hour dietary recall of 3 consecutive days at each survey Cumulative mean UPF intake NOVA classification (g/day) Gender, age, BMI, educational level, place of residence, regions, income level, smoking status, drinking status, metabolic equivalents, urbanicity, energy intake, and dietary factors (protein, total fat, carbohydrate, and sodium intake) Higher UPF consumption (4 th quartile of >36.1 g/day vs. 1 st quartile of <6.5 g/day(was associated with 17% increased risk for MetS (HR 1.17, 95% CI 1.01–1.35; p for trend = 0.047) Magalhães EIDS. (2022, Brazil) 56 The Ribeirão Preto birth cohort (14 y) n = 896 23-25 y (55.7%) Semi-quantitative 83-item FFQ (non-validated) NOVA classification (% of total kCal) NOVA classification (% of total food weight) Gender, age, skin color, educational level, marital status, household income, alcohol consumption, smoking status, physical activity, and energy intake UPF consumption had no association with MetS (% of kCal RR 1.00, 95% CI 0.99-1.01; % of weight RR 1.00, 95% CI 0.99-1.01) Cross-sectional studies Bezerra Barbosa L. (2023, Brazil) 59 Quilombos community-based survey n = 895 19-59 y (100%) 24-hour dietary recall NOVA classification (% of total kCal) NOVA score (ranging from 0 to 23) Model 3. Excess weight and neck circumference, plus variables from model 1 that showed p < 0.05 in the analysis for the aforementioned model - age and household income Higher UPF consumption (4 th quartile of 40.5% vs. 1 st quartile of 0.0%) was not associated with a higher prevalence of MetS (PR 1.09, 95% CI 0.89-1.32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, another cross‐sectional study of US adults found that MetS prevalence increased by 4% with a 10% increase in UPF intake (da Costa Louzada et al., 2015 ). However, a cohort study of Brazilian adults revealed no relationship between UPF and MetS risk (Magalhães et al., 2022 ). The difference in research sample and design can justify the difference in the mentioned study with previous studies and the present findings.…”
Section: Discussionmentioning
confidence: 99%